BIOLOGICAL DEGRADATION PROCESSES OF SUTURE MATERIALS USED IN SURGICAL DENTISTRY - Karimov Akobir Bahodirovich (Journal Park Publishing, 2025)
This article examines the biological degradation processes of various suture materials used in surgical dentistry. The study analyzes the resorption dynamics of absorbable and non-absorbable sutures, their interaction with oral tissues, and the factors influencing biodegradation, including enzymatic activity, pH of the oral environment, and inflammatory response. Comparative evaluation of silk, catgut, polyglycolic acid, and polylactic-based sutures revealed that synthetic absorbable materials demonstrate higher biocompatibility and predictable degradation patterns. The findings highlight the importance of selecting appropriate suture materials in pediatric and adult oral surgery to minimize postoperative inflammation and ensure optimal wound healing.
Keywords: Suture materials, surgical dentistry, biological degradation, resorption, biocompatibility, wound healing, oral tissue regeneration.